Optimization of On-Grid Rooftop PV Energy Utilization with Ev Charging Stations in Shopping Centers in West Kalimantan - Rizhal Ade Nugroho; Bambang Priyono (Green Publisher Indonesia, 2025)
The global shift toward renewable energy and electric mobility offers great potential for integrating photovoltaic (PV) systems with electric vehicle charging infrastructure. This study evaluates the feasibility and optimization of on-grid rooftop PV energy utilization with EV charging stations in shopping centers in West Kalimantan through an installation at Gaia Mall in Pontianak. Using HOMER Pro software, three scenarios were analyzed: Mall Only, SPKLU Only (electric vehicle charging stations), and combined Mall + SPKLU. The 1.16 MWp rooftop PV system produces around 1,524,240 kWh annually. The combined scenario emerged as the most optimal, with the lowest Net Present Cost (NPC) of IDR 29.8 billion, the highest Internal Rate of Return (IRR) at 10.3%, and a payback period of about 10 years. In this case, the mall’s yearly electricity use of 1,198,868 kWh is fully met. Excess energy of 325,372 kWh can supply about 15 SPKLU, each consuming 20,615 kWh per year. A 10,900 kWh lithium-ion battery storage system enhances supply stability and reliability. Environmentally, this combined system reduces carbon dioxide emissions by more than 1.8 million kilograms annually. The study demonstrates that integrating rooftop PV with EV charging stations is a technically viable, economically attractive, and environmentally sustainable solution aligning with Indonesia’s clean energy goals.